The New York times parent's guide to the best books for children - Lipson, Eden Ross (Three Rivers Press, 2000)
Provides reviews of more than one thousand classic children's books, ranging from picture books and early readers to young adult titles, along with more than fifty subject indexes and bibliographical listings of authors and illustrators.